Liquid-seed assisted synthesis of lamellar SAPO-n zeolite and its application on syngas to olefin conversion within bifunctional catalysis - Li Chen; Wenqian Jiao; Chuanming Wang; Haibo Zhou; Su Liu; Junjie Su; Yangdong Wang; Jun Yu; Zhaoteng Xue; Dongsen Mao (Catalysis Communications, 2023)
A liquid-seed assisted synthesis method was developed to prepare nano-sized lamellar SAPO-n zeolite. The aging of liquid-seed results in the dissolution of solid-seed particles and thus adjusts the ability to direct zeolite crystallization. Lamellar SAPO-34 zeolite with thickness of about 50 nm and well-controlled acidity was synthesized and the zeolite yield reaches 80% (SiO2/Al2O3 = 0.4, TEA/Al2O3 = 1.6, liquid-seed contents 3.35%). The bifunctional catalyst consisting of the above prepared SAPO-n and ZnCrOx oxide shows a high space-time yield (STY) of light olefins reaching 212 g•kg−1•h−1 in the reaction of direct conversion of syngas to light olefins.